Evolution of the hydrogen-bonding motif in the melamine–cyanuric acid co-crystal: a topological study - Petelski, Andre Nicolai (2016)
The melamine (M)/cyanuric acid (CA) supramolecular system is perhaps one of the most exploited in the field of self-assembly because of the high complementarity of the components. However, it is necessary to investigate further the factors involved in the assembly process. In this study, we analyzed a set of 13 Mn/CAm clusters (with n , m = 1, 2, 3), taken from crystallographic data, to characterize the nature of the hydrogen bonds involved in the self-assembly of these components as well as to provide greater understanding of the phenomenon. The calculations were performed at the B3LYP/6-311++G(d,p) and ω-B97XD (single point) levels of theory, and the interactions were analyzed within the framework of the quantum theory of atoms in molecules and by means of molecular electrostatic potential maps. Our results show that the stablest structure is the rosette-type motif and the aggregation mechanism is governed by a combination of cooperative and anticooperative effects. Our topological results explain the polymorphism in the self-assembly of coadsorbed monolayers of M and CA. [Figure not available: see fulltext.]